Forum on Drug Discovery, Development, and Translation: 2017 Annual Report - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
In 2017, the National Academies2019 Forum on Drug Discovery, Development, and Translation (the Forum) launched a three-part workshop series to explore a forward-looking agenda for generating and incorporating real-world evidence into medical product development and evaluation. The Forum also co-hosted the second workshop in a two-part series on the role of genetics in clinical drug development, further underscoring the critical role of precision medicine across the drug research and development lifecycle. For more information, please see https:\/\/www.nationalacademies.org\/our-work\/forum-on-drug-discovery-development-and-translation.

The Drug Development Paradigm in Oncology: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
Advances in cancer research have led to an improved understanding of the molecular mechanisms underpinning the development of cancer and how the immune system responds to cancer. This influx of research has led to an increasing number and variety of therapies in the drug development pipeline, including targeted therapies and associated biomarker tests that can select which patients are most likely to respond, and immunotherapies that harness the body2019s immune system to destroy cancer cells. Compared with standard chemotherapies, these new cancer therapies may demonstrate evidence of benefit and clearer distinctions between efficacy and toxicity at an earlier stage of development. However, there is a concern that the traditional processes for cancer drug development, evaluation, and regulatory approval could impede or delay the use of these promising cancer treatments in clinical practice. This has led to a number of efforts2014by patient advocates, the pharmaceutical industry, and the Food and Drug Administration (FDA)2014to accelerate the review of promising new cancer therapies, especially for cancers that currently lack effective treatments. However, generating the necessary data to confirm safety and efficacy during expedited drug development programs can present a unique set of challenges and opportunities. To explore this new landscape in cancer drug development, the National Academies of Sciences, Engineering, and Medicine developed a workshop held in December 2016. This workshop convened cancer researchers, patient advocates, and representatives from industry, academia, and government to discuss challenges with traditional approaches to drug development, opportunities to improve the efficiency of drug development, and strategies to enhance the information available about a cancer therapy throughout its life cycle in order to improve its use in clinical practice. This publication summarizes the presentations and discussions from the workshop.

Making Medicines Affordable: A National Imperative - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
Thanks to remarkable advances in modern health care attributable to science, engineering, and medicine, it is now possible to cure or manage illnesses that were long deemed untreatable. At the same time, however, the United States is facing the vexing challenge of a seemingly uncontrolled rise in the cost of health care. Total medical expenditures are rapidly approaching 20 percent of the gross domestic product and are crowding out other priorities of national importance. The use of increasingly expensive prescription drugs is a significant part of this problem, making the cost of biopharmaceuticals a serious national concern with broad political implications. Especially with the highly visible and very large price increases for prescription drugs that have occurred in recent years, finding a way to make prescription medicines2014and health care at large2014more affordable for everyone has become a socioeconomic imperative. Affordability is a complex function of factors, including not just the prices of the drugs themselves, but also the details of an individual's insurance coverage and the number of medical conditions that an individual or family confronts. Therefore, any solution to the affordability issue will require considering all of these factors together. The current high and increasing costs of prescription drugs2014coupled with the broader trends in overall health care costs2014is unsustainable to society as a whole. Making Medicines Affordable examines patient access to affordable and effective therapies, with emphasis on drug pricing, inflation in the cost of drugs, and insurance design. This report explores structural and policy factors influencing drug pricing, drug access programs, the emerging role of comparative effectiveness assessments in payment policies, changing finances of medical practice with regard to drug costs and reimbursement, and measures to prevent drug shortages and foster continued innovation in drug development. It makes recommendations for policy actions that could address drug price trends, improve patient access to affordable and effective treatments, and encourage innovations that address significant needs in health care.

Integrating Responses at the Intersection of Opioid Use Disorder and Infectious Disease Epidemics: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
According to the Centers for Disease Control and Prevention (CDC), 115 Americans die each day from an opioid overdose, which averages one death every 12.5 minutes. Between 1999 and 2016, the number of drug overdoses catapulted by 300 percent, with injection drug use increasing by 93 percent between 2004 and 2014 and opioid-related hospital admissions increasing by 58 percent over the past decade. And an inexorable sequela of the opioid epidemic is the spread of infectious diseases. To address these infectious disease consequences of the opioid crisis, a public workshop titled Integrating Infectious Disease Considerations with Response to the Opioid Epidemic was convened on March 12 and 13, 2018, by the National Academies of Sciences, Engineering, and Medicine. Participants discussed strategies to prevent and treat infections in people who inject drugs, especially ways to work efficiently though the existing public health and medical systems. This publication summarizes the presentations and discussions from the workshop.

Advancing Therapeutic Development for Pain and Opioid Use Disorders Through Public-Private Partnerships: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
Chronic pain is one of the most prevalent, costly, and disabling health conditions in the United States. Estimates show that more than 11 percent of the American population suffer from chronic pain, yet the federal pain research investment has been minimal. In parallel with a gradual increased recognition of the problems of treating chronic pain, the opioid epidemic has emerged as a growing public health emergency. The intersection of these two crises lies in the fact that an unintended consequence of treating pain has been an increasing number of opioid prescriptions and diversion of drugs for illicit purposes. In May 2017, the National Institutes of Health (NIH), and the National Institute on Drug Abuse announced a public2013private partnership to develop solutions to the opioid crisis and cut in half the time it takes to develop non-addictive analgesics. To advance the planning of NIH2019s anticipated public2013private partnerships, the National Academies2019 Forum on Neuroscience and Nervous Systems Disorders hosted a public workshop that brought together a diverse group of stakeholders from academia, federal agencies, advocacy organizations and companies developing therapeutics for pain and opioid use disorders. Participants discussed potential strategies to accelerate development of non-addictive pain medications and treatments for opioid use disorders. This publication summarizes the presentations and discussions from the workshop.

Enabling Novel Treatments for Nervous System Disorders by Improving Methods for Traversing the Blood–Brain Barrier: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
Despite substantial advances in developing treatments for the serious illnesses that affect people worldwide, there remains a tremendous unmet need in the treatment of complex neurologic diseases, including neuropsychiatric and neurodegenerative disorders. Chief among the challenges that have hindered the development of therapeutics for central nervous system (CNS) disorders is the blood2013brain barrier (BBB). The Forum on Neuroscience and Nervous System Disorders of the National Academies of Sciences, Engineering, and Medicine convened a workshop to explore the challenges associated with the BBB that have thus far stymied development of CNS drugs, examine new technologies that could address these challenges, and highlight potential opportunities for moving the field forward. This publication summarizes the presentations and discussions from the workshop.

Examining the Impact of Real-World Evidence on Medical Product Development: I. Incentives: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
On September 19201320, 2017, the National Academies of Sciences, Engineering, and Medicine held the first workshop of a three-part series titled Examining the Impact of Real-World Evidence on Medical Product Development. The workshops are intended to advance discussions and common knowledge among key stakeholders about complex issues relating to the generation and use of real-world evidence (RWE). The first workshop focused on how to align incentives to support the collection and use of RWE in health product review, payment, and delivery and how to address the barriers that impede the uptake and application of RWE. This publication briefly summarizes the presentations and discussions from the workshop.

Examining the Impact of Real-World Evidence on Medical Product Development: II. Practical Approaches: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
On March 620137, 2018, the National Academies of Sciences, Engineering, and Medicine held the second workshop of a three-part series titled Examining the Impact of Real-World Evidence on Medical Product Development. The workshops are intended to advance discussions and common knowledge among key stakeholders about complex issues relating to the generation and use of real-world evidence (RWE). The second workshop focused on practical approaches for the collection of real-world data (RWD)2014data generated outside of the traditional clinical trial setting2014and the use of RWE. This publication summarizes the presentations and discussions from this second workshop.

Impact of the Global Medical Supply Chain on SNS Operations and Communications: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
The Centers for Disease Control and Prevention (CDC) established the Strategic National Stockpile (SNS) with a focus on procuring and managing medical countermeasures (MCM) designed to address chemical, biological, radiological, and nuclear events and attacks by weapons of mass destruction. The stockpile is a repository of antibiotics, chemical antidotes, antitoxins, vaccines, antiviral drugs, and other medical materiel organized to respond to a spectrum of public health threats. Over time, the mission of the SNS has informally evolved to address other large-scale catastrophes, such as hurricanes or outbreaks of pandemic disease, and rare acute events, such as earthquakes or terror attacks. When disaster strikes, states can request deployment of SNS assets to augment resources available to state, local, tribal, or territorial public health agencies. CDC works with federal, state, and local health officials to identify and address their specific needs and, according to the stated mission of the SNS, ensure that the right resources reach the right place at the right time. On August 28, 2017, the National Academies of Sciences, Engineering, and Medicine convened a workshop to explore the current state of the global medical supply chain as it relates to SNS assets, and the role of communications in mitigating supply chain risks and in enhancing the resilience of MCM distribution efforts. This publication summarizes the presentations and discussions from the workshop.

Advancing the Science of Patient Input in Medical Product R&D: Towards a Research Agenda: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
On May 9, 2018, the National Academies of Sciences, Engineering, and Medicine held a workshop titled Advancing the Science of Patient Input in Medical Product R&D: Towards a Research Agenda. This workshop focused on the science of patient input for medical product research and development (R&D), with consideration of downstream regulatory and post-market decision making. The objectives of the workshop were to consider the current state of the science for soliciting and incorporating patient input into medical product R&D, explore gaps in knowledge and other barriers that impede progress, and discuss a potential framework for a research agenda for addressing gaps and barriers that could help move the field forward. This publication summarizes the presentations and discussions from the workshop.

Implementing and Evaluating Genomic Screening Programs in Health Care Systems: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
Genomic applications are being integrated into a broad range of clinical and research activities at health care systems across the United States. This trend can be attributed to a variety of factors, including the declining cost of genome sequencing and the potential for improving health outcomes and cutting the costs of care. The goals of these genomics-based programs may be to identify individuals with clinically actionable variants as a way of preventing disease, providing diagnoses for patients with rare diseases, and advancing research on genetic contributions to health and disease. Of particular interest are genomics- based screening programs, which will, in this publication, be clinical screening programs that examine genes or variants in unselected populations in order to identify individuals who are at an increased risk for a particular health concern (e.g., diseases, adverse drug outcomes) and who might benefit from clinical interventions. On November 1, 2017, the National Academies of Sciences, Engineering, and Medicine hosted a public workshop to explore the challenges and opportunities associated with integrating genomics-based screening programs into health care systems. This workshop was developed as a way to explore the challenges and opportunities associated with integrating genomics-based programs in health care systems in the areas of evidence collection, sustainability, data sharing, infrastructure, and equity of access. This publication summarizes the presentations and discussions from the workshop.

Public Health Consequences of E-Cigarettes - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
Millions of Americans use e-cigarettes. Despite their popularity, little is known about their health effects. Some suggest that e-cigarettes likely confer lower risk compared to combustible tobacco cigarettes, because they do not expose users to toxicants produced through combustion. Proponents of e-cigarette use also tout the potential benefits of e-cigarettes as devices that could help combustible tobacco cigarette smokers to quit and thereby reduce tobacco-related health risks. Others are concerned about the exposure to potentially toxic substances contained in e-cigarette emissions, especially in individuals who have never used tobacco products such as youth and young adults. Given their relatively recent introduction, there has been little time for a scientific body of evidence to develop on the health effects of e-cigarettes. Public Health Consequences of E-Cigarettes reviews and critically assesses the state of the emerging evidence about e-cigarettes and health. This report makes recommendations for the improvement of this research and highlights gaps that are a priority for future research.

Review of Report and Approach to Evaluating Long-Term Health Effects in Army Test Subjects - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
Between 1942 and 1975, the U.S. Army conducted tests on human subjects to study the effects of a variety of agents, including chemical warfare agents, biological agents, medications, vaccines, and other substances. The tests investigated the immediate or short-term health effects from acute exposure to understand vulnerabilities to attack. Whether the exposures could have resulted in long-term health consequences to the test subjects has been assessed periodically, and the Army is required to notify subjects of information relating to potential health effects associated with exposure to the test agents. Most recently, a 2016 court injunction directed the Army to provide test subjects with new information about potential long-term health effects associated with their exposures, and to provide medical care if an injury or illness could be attributed to their participation in an Army chemical or biological testing program. In support of the first requirement, the Army contracted a report, Assessment of Potential Long-Term Health Effects on Army Human Test Subjects of Relevant Biological and Chemical Agents, Drugs, Medications and Substances: Literature Review and Analysis (the Report), to determine whether new information published since 2006 should be provided to the veterans. At the request of the Army, the National Academies of Sciences, Engineering, and Medicine formed an ad hoc committee that was tasked with conducting an independent review of the Report. The committee assessed whether the Report appropriately identified potential long-term health effects that could have resulted from test exposures using an adequate weight-of-evidence approach. The general approach for evaluating agent- and outcome-specific associations as outlined in the Army Memorandum was also reviewed. An interim report of its overarching findings and their supporting evidence was prepared in February 2018. This final report provides additional detail about the basis of the committee2019s findings and recommendations. No new findings or recommendations have been added to this report.

Artificial Intelligence and Machine Learning to Accelerate Translational Research: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
The big data revolution, accompanied by the development and deployment of wearable medical devices and mobile health applications, has enabled the biomedical community to apply artificial intelligence (AI) and machine learning algorithms to vast amounts of data. This shift has created new research opportunities in predictive analytics, precision medicine, virtual diagnosis, patient monitoring, and drug discovery and delivery, which has garnered the interests of government, academic, and industry researchers alike and is already putting new tools in the hands of practitioners. This boom in digital health opportunities has also raised numerous questions concerning the future of biomedical research and healthcare practices. How reliable are deployed AI-driven diagnostic tools, and what is the impact of these tools on doctors and patients? How vulnerable are algorithms to bias and unfairness? How can research improve the process of detecting unfairness in machine learning algorithms? How are other fields simultaneously advancing AI applications? How will academia prepare scientists with the skills to meet the demands of the newly transformed industry? Informed answers to these and other questions require interdisciplinary discussion and collaboration. On February 13 and 14, 2018, the National Academies of Sciences, Engineering, and Medicine convened a workshop to explore these and other questions related to the emerging use of AI and machine learning technologies in translational research. This publication summarizes the presentations and discussions from the workshop.

Review of Report and Approach to Evaluating Long-Term Health Effects in Army Test Subjects: Interim Report - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
Between 1942 and 1975, the U.S. Army conducted tests with human subjects to study the effects of a variety of agents, including chemical warfare and biological agents. The potential long-term health effects on the test subjects from their exposures have been evaluated periodically, most recently in a report titled Assessment of Potential Long-Term Health Effects on Army Human Test Subjects of Relevant Biological and Chemical Agents, Drugs, Medications and Substances: Literature Review and Analysis (the Report), which was prepared by a contractor to assist the Army with making determinations about providing medical care to former test subjects. In response to a request by the Army, the National Academies of Sciences, Engineering, and Medicine formed a committee that was tasked with examining whether the Report appropriately identified potential long-term health effects from exposure to the test agents and whether an adequate weight-of-evidence approach was used to characterize the strength of the associations between the agents and their potential health effects. The committee was made aware at its first meeting on November 30, 2017, that the Army had already begun to receive applications for medical care and that some determinations may need to be made before the committee's evaluation of the Report was completed. Because of this urgency, the Army developed a process by which applications for medical care will be reviewed, and as a result, the committee was given the additional task of reviewing the Army's Memorandum that describes the approach that will be used by the Army to evaluate agent- and outcome-specific associations. This interim report was prepared to facilitate the Army's deliberations. A review of the Report is presented first, followed by a review of the Memorandum.

Report of the Committee on Proposal Evaluation for Allocation of Supercomputing Time for the Study of Molecular Dynamics: Ninth Round - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
This report describes the work of the Committee on Proposal Evaluation for Allocation of Supercomputing Time for the Study of Molecular Dynamics, Ninth Round. The committee evaluated submissions received in response to a Request for Proposals (RFP) for biomolecular simulation time on Anton 2, a supercomputer specially designed and built by D.E. Shaw Research (DESRES). Over the past 8 years, DESRES has made an Anton or Anton 2 system housed at the Pittsburgh Supercomputing Center (PSC) available to the non-commercial research community, based on the advice of previous National Research Council committees. As in prior rounds, the goal of the ninth RFP for simulation time on Anton 2 is to continue to facilitate breakthrough research in the study of biomolecular systems by providing a massively parallel system specially designed for molecular dynamics simulations. The program seeks to continue to support research that addresses important and high impact questions demonstrating a clear need for Anton's special capabilities. Report of the Committee on Proposal Evaluation for Allocation of Supercomputing Time for the Study of Molecular Dynamics, Ninth Round is the final report of the committee's evaluation of proposals based on scientific merit, justification for requested time allocation, and investigator qualifications and past accomplishments. This report identifies the proposals that best met the selection criteria.

Medical Product Shortages During Disasters: Opportunities to Predict, Prevent, and Respond: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
In response to the shortage of intravenous (IV) saline solution that was exacerbated during the 2017 hurricane season, the Office of the Assistant Secretary for Preparedness and Response (ASPR) at the Department of Health and Human Services (HHS) asked the National Academies of Sciences, Engineering, and Medicine to convene a workshop to better understand the gaps that led to cascading effects in patient care throughout the U.S. health care system. This publication summarizes the presentations and discussions from the workshop.

Medication-Assisted Treatment for Opioid Use Disorder: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
On October 30 and 31, 2018, the National Academies of Sciences, Engineering, and Medicine held a 1.5-day workshop on Medication-Assisted Treatment (MAT) for Opioid Use Disorder (OUD). The workshop participants reviewed the current knowledge and gaps in understanding regarding the effectiveness of MAT for treating OUD, examined the available evidence on the range of parameters and circumstances in which MAT can be effectively delivered (e.g., duration of treatment, populations, settings, and interventions to address social determinants of health as a component of MAT), identified challenges in implementation and additional research needed. This publication summarizes the presentations and discussions from the workshop.

Advancing Disease Modeling in Animal-Based Research in Support of Precision Medicine: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
Precision medicine is focused on the individual and will require the rapid and accurate identification and prioritization of causative factors of disease. To move forward and accelerate the delivery of the anticipated benefits of precision medicine, developing predictable, reproducible, and reliable animal models will be essential. In order to explore the topic of animal-based research and its relevance to precision medicine, the National Academies of Sciences, Engineering, and Medicine convened a 2-day workshop on October 5 and 6, 2017. The workshop was designed to focus on the development, implementation, and interpretation of model organisms to advance and accelerate the field of precision medicine. Participants examined the extent to which next-generation animal models, designed using patient data and phenotyping platforms targeted to reveal and inform disease mechanisms, will be essential to the successful implementation of precision medicine. This publication summarizes the presentations and discussions from the workshop.

Collaborations of Consequence: NAKFI's 15 Years Igniting Innovation at the Intersections of Disciplines (The National Academies Press, 2018)
This publication represents the culmination of the National Academies Keck Futures Initiative (NAKFI), a program of the National Academy of Sciences, the National Academy of Engineering, and the National Academy of Medicine supported by a 15-year, 40 million grant from the W. M. Keck Foundation to advance the future of science through interdisciplinary research. From 2003 to 2017, more than 2,000 researchers and other professionals across disciplines and sectors attended an annual 201cthink-tank201d style conference to contemplate real-world challenges. Seed grants awarded to conference participants enabled further pursuit of bold, new research and ideas generated at the conference.